3D hypothetical reconstruction of a Neolithic hut from the waterlogged site of La Draga (Banyoles, Spain) - Evdoxia Tzerpou; Ivan Campana; Jan Salazar; Oriol López-Bultó; Antoni Palomo; Raquel Piqué; Xavier Terradas; Juan A. Barceló (Virtual Archaeology Review)
This paper presents a hypothetical digital reconstruction of a prehistoric wooden hut from the archaeological site of La Draga (Banyoles, Northeast Iberia). La Draga is a waterlogged Early Neolithic settlement (ca. 7300-6700 years ago), located on the eastern shore of lake Banyoles, and presents an extraordinary preservation of wood and vegetal materials usually not recovered in prehistoric archaeology. The wooden architectonical elements recovered in La Draga were analysed and the information extracted has been used to create a 3D hypothetical reconstruction of the pile dwellings constructed and used by the inhabitants of La Draga in prehistoric times. The multidisciplinary research team working in La Draga has produced a significantly wide panorama of the elements composing this Neolithic site, including paleovegetation and paleoenvironmental studies, analysis of artefacts, and spatial organisation. This paper reproduces the reasoning behind the geometric completion of architectural form and texturing of the digital model. The methodology employed includes the creation of successive layers of development of the 3D model, enriched with archaeological information and with the gradually increased participation of the human expert in the interpretation and visualisation of data. A basic spatial model was constructed first, the architectural model of the base plane of the structure was then modelled, and finally, it followed the overhead plane of the structure. Two different modelling software –Rhinoceros 3D and Blender– were employed during the process and provided different renderings of the final model. Emphasis is also on the degree of uncertainty of the final hypothetical reconstruction and on the use of computer simulation techniques to increase reliability. In this paper, the knowledge-based decision-making process was based on datasets, logical deductions, as well as on assumptions. All decisions to add substantive information to the hypothetical reconstruction have been explained to ensure the scientific rigour and transparency of the reconstruction.